Evaluation Report on the Working of Lok Karya Kshetras - Planning Commission (Planning Commission, 1967)
The Programme Evaluation Organisation undertook an evaluation of L.K.Ks in 1960 at the instance of the Planning Commission which provides grants for this programme. As the programme expanded considerably since then, the P.E.O. was again requested to conduct a second evaluation study, the findings of which are presented in this report.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission